A Project-based Approach to FPGA-aided Teaching of Digital Systems - Fajar Suryawan (IAES Indonesia Section, 2017)
This article shares experience and lessons learned in teaching course on programmable logic design at Universitas Muhammadiyah Surakarta, Indonesia This course is part of bachelor of engineering (electrical) degree program. Project- based approach is chosen to strengthen these students’ un- derstanding and practical skills. Each year’s project involves challenges for the students to solve by implementing digital system on an FPGA design board. Here, background and curriculum context of the course will be presented. The projects and their challenges will be discussed. Finally, lessons learned and future improvement on the student projects will be discussed. Index Terms—project-based learning, field programmable gate arrays, education, programmable logic design, hardware design languages, laboratories